Prognostic indicators for perioperative survival after diaphragmatic herniorrhaphy in cats and dogs: 96 cases (2001-2013). Issue 1 (December 2016) - Legallet, Claire; Thieman Mankin, Kelley; Selmic, Laura
Abstract Background To determine associations between perioperative mortality after surgery for traumatic diaphragmatic hernia, medical records of 17 cats and 79 dogs that underwent diaphragmatic herniorrhaphy were reviewed. Results The combined perioperative survival rate was 81.3% (88.2% in cats and 79.8% in dogs). Data from acute and chronic cases was assessed separately. Of the acute cases (12 cats and 48 dogs), 10 cats (83.3%) and 38 dogs (79.2%) survived to discharge. Of the chronic cases (5 cats and 31 dogs), 5 cats (100%) and 25 dogs (80.6%) survived to discharge. The time between trauma and surgery, trauma and admission, and admission and surgery were not associated with survival. For cats and dogs, increased duration of anesthesia and surgical procedure were associated with increased mortality (P  = 0.0013 and 0.004, respectively). Animals with concurrent soft tissue injuries had a 4.3 times greater odds of mortality than those without soft tissue injury (P  = 0.01). Animals with concurrent soft tissue and orthopedic injuries had a 7.3 times greater odds of mortality than those without soft tissue and orthopedic injuries (P  = 0.004). Animals that were oxygen dependent had a 5.0 times greater odds of mortality than those that were not (P  = 0.02). No other variables were significantly associated with survival. Conclusions For cats and dogs that underwent surgery for traumatic diaphragmatic hernia, increased anesthetic duration, increased duration of surgical procedure, concurrent soft tissue injuries, concurrent soft tissue and orthopedic injuries, and perioperative oxygen dependence were associated with increased mortality.